PENGEMBANGAN POTENSI DESA CEMAGI KECAMATAN MENGWI KABUPATEN BADUNG DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT - I Made Hedy Wartana; Made Yudi Darmita; Gde Herry Sugiarto; Desak Made Purnama Dewi (Universitas Triatma Mulya, 2022)
Cemagi Village is one of the villages in the Mengwi sub-district, Badung district, which has a coast. The people of Cemagi village have various professions, namely those who work in the agricultural sector, as breeders, work in the tourism sector, fisheries, as MSME actors and so on. .. In Cemagi Village there are several financial institutions that have an important role in supporting the economy in Cemagi Village. Cemagi Village has a geographical location that is very easy to reach because it is the route to the Tanah Lot Temple tourist attraction in Tabanan. In the village of Cemagi, several inns and villas have also been built. Local residents have started making inns and some are contracting out their land to build villas which will later be rented out to tourists. Seeing the conditions and existence of the Cemagi village, Cemagi village has great prospects to be developed into a tourist area in order to improve the community's economy. The methods used in this community service are counseling and mentoring methods so that there is direct interaction with MSME actors in Cemagi village, Managers of Financial Institutions in Cemagi village, Cemagi Village Communities and Cemagi village government. The problems found in Cemagi village include: 1) The MSME empowerment in Cemagi village has not been maximized in the development of Cemagi Village as a tourist destination. 2) The utilization of financial institutions in Cemagi village has not been optimal to support the capital of MSME actors in Cemagi village. 3). Management of Mengening Beach and Seseh Beach is not yet optimal as an attraction for tourists. In implementing this community service program, the executors immediately go down to the location to directly see the conditions in the field and coordinate and discuss the problems faced by partners in Cemagi village. their villages and being able to do good cooperation with financial institutions in Cemagi village and more organized Mengening Beach and Seseh Beach by optimizing cooperation with stake holders so that Mengening Beach and Seseh Beach can be managed optimally so that they are more attractive for tourists to visit